Treatment of textile wastewater by SCWO in a tube reactor - Sogut, Onur O.; Akgun, Mesut (ELSEVIER, 2007)
Oxidation of aqueous solutions of a model azo dye pollutant (Cl Disperse Orange 25) was studied in a continuous flow reactor, operated at temperatures between 400 and 600 degrees C and at a fixed pressure of 25 MPa. The parameters used were the temperature, dye concentration, oxidant concentration and flow rate. The initial dye concentrations were in the range of 24.25 x 10(-3) and 121.25 x 10(-3) mol L-1 in terms of chemical oxygen demand (COD). Hydrogen peroxide (H2O2) was used as a source of oxygen, and the initial oxidant concentrations were between 36.75 x 10(-3) and 183.75 x 10(-3) mol L-1. The results demonstrated that the supercritical water oxidation (SCWO) process decreases the chemical oxygen demand up to 98.52% in very short reaction times (at a residence time of 4-12 s). Global rate expression according to wastewater and oxidant concentration was regressed from the complete set of data. The first-order global rate expression was determined with an activation energy of 27.8(+/- 1.2) kJ mol(-1) and a pre-exponential factor of 34.3(+/- 1.5) s(-1) to a 95% confidence level. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: SCWO; oxidation kinetic; textile wastewater; disperse orange 25; COD; CATALYTIC WET OXIDATION; AZO-DYE; AQUEOUS-SOLUTIONS; AIR OXIDATION; DECOLORIZATION; DECOMPOSITION; DEGRADATION; OZONATION; Chemistry; Engineering